Role of Pelvic Lymph Node Resection in Vulvar Squamous Cell Cancer: A Subset Analysis of the AGO-CaRE-1 Study - Woelber, Linn; Bommert, Mareike; Harter, Philipp; Prieske, Katharina; zu Eulenburg, Christine; Jueckstock, Julia; Hilpert, Felix; de Gregorio, Nikolaus; Iborra, Severine; Sehouli, Jalid; Ignatov, Atanas; Hillemanns, Peter; et al. (Annals of Surgical Oncology, 2021)
Background: As the population at risk for pelvic nodal involvement remains poorly described, the role of pelvic lymphadenectomy (LAE) in vulvar squamous cell cancer (VSCC) has been a matter of discussion for decades. Methods: In the AGO-CaRE-1 study, 1618 patients with International Federation of Gynecology and Obstetrics (FIGO) stage IB or higher primary VSCC treated at 29 centers in Germany between 1998 and 2008 were documented. In this analysis, only patients with pelvic LAE (n = 70) were analyzed with regard to prognosis and correlation between inguinal and pelvic lymph node involvement. Results: The majority of patients had T1b/T2 tumors (n = 47; 67.1%), with a median diameter of 40 mm (2–240 mm); 54/70 patients (77.1%) who received pelvic LAE had positive groin nodes. For 42 of these 54 patients, the number of affected groin nodes had been documented as a median of 3; 14/42 (33.3%) of these patients had histologically confirmed pelvic nodal metastases (median number of affected pelvic nodes 3 [1–12]). In these 14 patients, the median number of affected groin nodes was 7 (1–30), with a groin metastases median maximum diameter of 42.5 mm (12–50). Receiver operating characteristic analysis showed an area under the curve of 0.85, with 83.3% sensitivity and 92.6% specificity for the prediction of pelvic involvement in cases of six or more positive groin nodes. No cases of pelvic nodal involvement without groin metastases were observed. Prognosis in cases of pelvic metastasis was poor, with a median progression-free survival of only 12.5 months. Conclusion: For the majority of node-positive patients with VSCC, pelvic nodal staging appears unnecessary since a relevant risk for pelvic nodal involvement only seems to be present in highly node-positive disease.
CRIS-Team Scopus Importer:2021-04-02